2016
DOI: 10.1038/srep39190
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages Enhance Migration in Inflammatory Breast Cancer Cells via RhoC GTPase Signaling

Abstract: Inflammatory breast cancer (IBC) is the most lethal form of breast cancer. All IBC patients have lymph node involvement and one-third of patients already have distant metastasis at diagnosis. This propensity for metastasis is a hallmark of IBC distinguishing it from less lethal non-inflammatory breast cancers (nIBC). Genetic profiling studies have been conducted to differentiate IBC from nIBC, but no IBC cancer-cell-specific gene signature has been identified. We hypothesized that a tumor-extrinsic factor, not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 43 publications
(79 reference statements)
2
48
0
Order By: Relevance
“…Recently, elegant work by Shiao et al, using the orthotopic MMTV-PyMT mouse model of mammary carcinogenesis, showed that polarized TH2 macrophages and CD4þ T cells mediated tumor growth after radiation therapy, in part via suppression of CD8þ T cells (8). Further, Allen et al (9) recently reported that IL6, IL8, and IL10 from macrophage-derived conditioned medium enhanced migration of IBC cells. These findings suggest that macrophages have a role in the sensitivity of IBC cells to radiation, but this question has not yet been examined in great detail.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, elegant work by Shiao et al, using the orthotopic MMTV-PyMT mouse model of mammary carcinogenesis, showed that polarized TH2 macrophages and CD4þ T cells mediated tumor growth after radiation therapy, in part via suppression of CD8þ T cells (8). Further, Allen et al (9) recently reported that IL6, IL8, and IL10 from macrophage-derived conditioned medium enhanced migration of IBC cells. These findings suggest that macrophages have a role in the sensitivity of IBC cells to radiation, but this question has not yet been examined in great detail.…”
Section: Introductionmentioning
confidence: 99%
“…We found that miR‐138 inhibits osteogenesis and matrix mineralization and noted that cell proliferation, cell shape, and cell migration were also affected. Analysis of potential miR‐138 target genes led us to pursue one specific target, RhoC, because this small‐molecular‐weight GTPase has been implicated in altering cell shape via regulation of the actin cytoskeleton, in addition to regulating processes controlling cell proliferation, migration, and invasion in other systems . Here, we have discovered a new mechanism in DDCs, whereby miR‐138 functions to suppress RhoC expression, which in turn inhibits F‐actin polymerization and the ability of these cells to proliferate, possibly migrate, and differentiate toward the osteogenic lineage.…”
Section: Introductionmentioning
confidence: 99%
“…The Rho-like family of Rho-GTPases have been well characterized for their participation in the progression of breast cancer 32,3436 and the alteration of metabolic phenotype 33 . Therefore, we next applied our imaging and analysis strategy to explore the potential for fragmented mitochondria in breast cancer cells that lack either the Rho-like family of Rho-GTPases RhoA or RhoC, via CRISPR/Cas9 knockout (WT, RhoA KO, RhoC KO) ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%